Surface functionalization of carbon quantum dots from hydrothermal synthesis of iota carrageenan - De Yro, Persia Ada N.
Carbon quantum dots (CQDs) with fascinating properties have gradually become a promising new nanocarbon member due to their nonthreatening, abundant and inexpensive nature. This study demonstrated an innovative and facile approach of producing and functionalizing CQDs from iota carrageenan with significant high quantum yields to produce fluorescent CQDs for bio imaging applications. CQDs from iota carrageenan were synthesized via hydrothermal method with quantum yields up to 17%. Doping the CQDs with nitrogen by the addition of tetraethylene pentamine (TEPA) produced N-CQDs with a quantum yield of 77%. Infrared spectral analyses confirmed the formation of hydroxyl, carboxylic and carbonyl functional groups which was further verified by Time of Flight Secondary Ion Spectroscopy (ToFSIMS). Presence of amine groups can also be found on the N-CQDs produced with TEPA. The CQDs and N-CQDs, have crystalline graphitic structures, and sizes ranging from 2 to 10nm. The iota carrageenan molecules after hydrolysis and a series of dehydration are broken down to produce aromatic clusters. A nucleus grows from these clusters and form CQD that has an outer surface which contains high concentration of reactive oxygen groups while the core oxygen forms less reactive groups. The synthesized CQD has smaller size, blue fluorescence emission, shorter p emissions, higher E, higher frequency, lower A and bigger band gap while the synthesized N-CQD has bigger size, longer p system, lower E, lower frequency, higher A and shorter band gap. Doping more N into CQDs facilitates the growth of carbon core, allowing the formation of larger N-CQD. CQD properties greatly depend on their size due to the quantum confinement effect and the variation in density and nature functional groups available. In addition to this, the energy band gap can also be tuned by changing the size of the CQD. The CQDs were tested for nano probe applications, thru labelling and detection of E.coli. The functional groups present in the CQD surface form H-bonds with the hydroxyl groups on the E. Coli surface. The E.coli fluoresced, proving that CQDs serve as effective probe for bio-imaging application. This study successfully produced and functionalized CQD. With the simple synthetic method of production and understanding of the fluorescence mechanism of CQD, the possibilities of producing CQD with higher quantum yield is promising.